UPAYA MENINGKATKAN KOMPETENSI BELAJAR PPKN MATERI PEMBUKAAN UUD 1945 DENGAN METODE MAKE A MATCH PADA SISWA KELAS IX SMP NEGERI 3 COLOMADU SEMESTER 1 TAHUN PELAJARAN 2019/2020 - Supanti Supanti (ITB AAS INDONESIA Surakarta, 2020)
Background of the lack of active involvement of students in learning there are at least three indicators that indicate this. First, students lack the courage to express opinions to others. Second, students lack the ability to formulate their own ideas. and third, students are not accustomed to competing to express their opinions with other friends. These problems eventually led to the achievement of student learning competencies to be low. The problems examined were formulated as follows: how is the effort to improve the learning competence of PPKn in the opening of the 1945 Constitution with the Make A Match method in class IX students of SMP Negeri 3 Colomadu Karanganyar Semester 1 2019/2020 Academic Year. This research method uses a classroom action research model (CAR). The subjects in this study were all students of class IX SMPN 3 Colomadu in Academic Year 2019/2020. Data collection techniques using observation, questionnaires, and documentation. Data analysis techniques using comparative analysis and critical analysis. The results showed that the implementation of learning using the Make A Match method could improve the PPKn learning competence in the Opening of the 1945 Constitution in class IX students of SMP Negeri 3 Colomadu Karanganyar Semester 1 2019/2020 Academic Year. Student knowledge competence at the end of the second cycle reaches an average of 85.8, has exceeded the established performance indicators that is equal to 80. Attitude competence at the end of the second cycle reaches an average of 3.4 (active attitude) and student skills competency at the end of the cycle II reached an average of 89.1 (very good), so this action research was declared successful. Achievement of performance indicators in cycle II shows that the application of the Make A Match learning method is effective in increasing student learning competency. The suggestion for PPKn teachers is that they need to increase their knowledge about the variety of learning methods. This will help the teacher to be able to improve the quality of the process and student learning outcomes in the learning process. The use of the Make A Match learning method can be an alternative to increasing learning effectiveness. Keywords: Learning Competence, Make A Match